Promoting Exercise as Part of a Physiotherapy‐Led Falls Pathway Service for Adults with Intellectual Disabilities: A Service Evaluation. Issue 3 (1st September 2014) - Crockett, Jennifer; Finlayson, Janet; Skelton, Dawn A.; Miller, Gillian
<x xml:space="preserve">Abstract</x> Background People with intellectual disabilities experience high rates of falls. Balance and gait problems are common in people with intellectual disabilities, increasing the likelihood of falls; thus, tailored exercise interventions to improve gait and balance are recommended. The present authors set up a physiotherapy‐led falls pathway service (FPS) for clients with intellectual disabilities to promote exercise and prevent falls. Method Fifty clients with intellectual disabilities were referred in an 18‐month period, 35 (70%) were prescribed exercise and 27 (54%) completed the exercise programme. The FPS was evaluated using the following outcome measures: Tinetti score, number of falls, clinician's judgement and carer's judgement. Results Improvement in balance and mobility and a decrease in the number of falls were reported post‐exercise intervention. Conclusion Physiotherapists have a key role to play in promoting exercise to prevent falls in services for people with intellectual disabilities. This evaluation suggests positive outcomes for these clients to reduce or prevent further falls.